Marketing Kit bagi UMKM - Yusuf, Ramayani; Veranita, Mira; Syahidin, Yuda; Hernawati, Euis (Journal Pemberdayaan Masyarakat Indonesia, 2022)
The impact of social media in assessing a product's brand strength can no longer be ignored. The purpose of this paper is to describe Sorai Steamboat n Grill's community service efforts. To make it easier for MSMEs to advertise their products, marketing kits in the shape of logos, business cards, posters, and other promotional media are created. A marketing kit is an effective instrument for initiating product promotion operations. The requirements research, planning, creation of marketing kits, and mentoring of MSMEs are all part of the community service stage.The marketing kit was created without a hitch owing to the proprietor of Sorai Steamboat n Grill's helpful cooperation. The number of Instagram followers grew, the brand was strengthened, and revenue increased as a result of this action.